Human resources development redicalism in the service sector - Srivastava, M P (New Delhi Gyan Publishing House, 2000)
This book is an attempt to focus on two major issues facing the service sector in general and sub-sector of telecommunication banks and railways.the first issues relates to the growth and development of service sector and how for the human resources engag
Keywords: Manpower; Manpower policy; Education; Economics